Pengembangan Video Profil Terminal Wisata Grafika Cikole Lembang - Bambang Perdana, Bayu; Hamzah, Faizal (Media Wisata, 2025)
The purpose of this research is to develop a video profile of the Terminal Wisata Grafika Cikole as an information and promotional medium in the city of Bandung. Terminal Wisata Grafika Cikole is a popular tourist destination in the region of Cikole, but it lacks an effective promotional medium. Therefore, this research attempts to fill that gap by creating an informative and appealing video profile. The method used in this research is qualitative descriptive research with a case study approach. Data were collected through observations, interviews, and the analysis of documents related to Terminal Wisata Grafika Cikole. The research findings indicate that the developed video profile depicts the beauty and products available at the terminal, as well as informs visitors about the activities and services they can enjoy. This video profile is expected to be an effective tool in promoting the Terminal Wisata Grafika Cikole, attracting potential tourists, and providing the necessary information to the audience. Furthermore, it can also be used by relevant parties in their efforts to promote tourism in the city of Bandung as a whole. Therefore, this research has a positive impact on the development of the tourism industry in Bandung.